Optimalisasi Sistem Operasi Windows Agar Pengguna Memanfaatkan Layanan Lingkungan Cloud Dan Edge Computing - Rakhmadi Rahman; Muhammad Yusuf Dzaky .J; Jesica Septiani Manurung (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Optimizing Windows-based operating systems for databases in Cloud and Edge Computing environments is very important to increase data management efficiency and performance. In this study, we discuss ways to optimize Windows in both environments. In the Cloud environment, the main focus is on data management using services such as Google Drive, while in the Edge environment, optimization is carried out using Windows IoT Core and Windows IoT Enterprise. Of these two, we optimize Windows IoT Enterprise more because it is more directed towards Edge computing. Our research results show that by implementing the right optimization and efficient performance results, database performance can be significantly improved, which provides great benefits for individual users and society